A new MAP channel decoder trellis path metric for a CDMA mobile subject to channel estimation errors - Messier, G.G.; Krzymien, W.A. (2004 IEEE Itnernational Conference on Communications, 2004)
A new trellis path metric is derived for the CDMA mobile MAP and logMAP turbo decoders. This metric accounts for the non-Gaussian received symbol probability distribution seen at the output of a mobile RAKE receiver when the RAKE combining weights are subject to channel estimation error. Since an exact analytical expression for this distribution is difficult to find, the metric is instead derived by finding the characteristic function of an approximation to the distribution. Simulations are then used to compare how the CDMA forward link performs when the mobile uses either the conventional logMAP trellis path metric or the new metric. The results indicate that while the conventional metric is still the best choice when channel estimation error is small, the new metric provides a significant performance improvement when channel estimation error is large.